-4x+-4-9=-12x+11

Simple and best practice solution for -4x+-4-9=-12x+11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4x+-4-9=-12x+11 equation:


Simplifying
-4x + -4 + -9 = -12x + 11

Reorder the terms:
-4 + -9 + -4x = -12x + 11

Combine like terms: -4 + -9 = -13
-13 + -4x = -12x + 11

Reorder the terms:
-13 + -4x = 11 + -12x

Solving
-13 + -4x = 11 + -12x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '12x' to each side of the equation.
-13 + -4x + 12x = 11 + -12x + 12x

Combine like terms: -4x + 12x = 8x
-13 + 8x = 11 + -12x + 12x

Combine like terms: -12x + 12x = 0
-13 + 8x = 11 + 0
-13 + 8x = 11

Add '13' to each side of the equation.
-13 + 13 + 8x = 11 + 13

Combine like terms: -13 + 13 = 0
0 + 8x = 11 + 13
8x = 11 + 13

Combine like terms: 11 + 13 = 24
8x = 24

Divide each side by '8'.
x = 3

Simplifying
x = 3

See similar equations:

| 35=8-9y | | -p^2-2p=0 | | 2(j-7)=64 | | 3y-8=9 | | 2x+4(x+3)=36 | | 4e^3x+6=30 | | -3x-3x=26-2 | | 8c-13=3c+36 | | 2u^2-3u=0 | | -9=k-5k+7 | | 4x^2-15=25 | | 6t+17-3t=38 | | -6w+14=-76 | | 11x+22x-2y+54y= | | 0.5a-5-0.5a= | | -f^2+5f=0 | | 3-8p=29 | | 6(x+3)-9(x-1)=5-(X+3) | | 6t+17-3r=38 | | n-2n=n-4 | | 7r^2-5=0 | | G+14.8=45 | | 4x-2y=1forsubjecty | | 6(h-5+7)=2h+52 | | 6-16=-2z | | 60x=210 | | Y^2-15=3y+25 | | 4x+5y=841 | | -5x+-15x=-30 | | 4(t+8)-35= | | -3(f-4)=36 | | 47-(7)2= |

Equations solver categories